Assessment of microbial quality, adulterants and preservatives in pasteurized milk - Bhagyalakshmi P S (Department of Veterinary Public Health, College of Veterinary and Animal Sciences, 2008)
In the present study 200 pasteurized milk samples were collected from the retail shops of Thrissur and Palakkad districts. From Thrissur district, 20 samples each were collected from five brands viz., A, B, C, D and E, and an equal number of samples were obtained from the brands F, G, H, I and J of Palakkad district. All the samples were analyzed for the microbial quality by estimating various bacterial counts and yeast and mould count and also assessed the presence of certain pathogenic and spoilage bacteria. The milk samples were also tested to detect the presence of adulterants viz., starch and cane sugar and preservatives like carbonates and formaldehyde.